Short-term debt catering - Lugo, Stefano (Journal of Corporate Finance, 2021)
Focusing on investments by US money market mutual funds (MMFs) in nonfinancial commercial paper, this study shows that the demand for corporate short-term securities by preferred-habitat investors is positively associated with the use of short-term debt by firms. Consistent results are found when using a longitudinal dataset with a monthly frequency and a firm-quarter panel dataset; instrumenting the demand by MMFs; measuring the demand by MMFs at the level of individual issuers; and exploiting an exogenous change in regulation for identification. These findings support the idea that corporations cater to investors' preferences in choosing their debt maturity structure.